Bio-waste Alchemy: Turning Agricultural Residue into Green Gold for Food Packaging, A Systematic Review - Ulhusna, Annisa; Amir, Reza Mardhiyah; Yusmaidi, Nuridayah (Green Engineering Society, 2025)
The increasing environmental concerns associated with conventional plastic packaging have accelerated the global pursuit of sustainable alternatives. This review explored the innovative transformation of agricultural waste into eco-friendly food packaging materials, highlighting its potential to address both ecological and economic challenges. Agricultural residues—such as cereal by-products, sugar and starch crop wastes, fruit processing leftovers, and leaf waste—were rich in biopolymers like cellulose, starch, and pectin, making them suitable candidates for biodegradable packaging. Through advancements in green chemistry, biotechnology, and materials science, these wastes are now being repurposed into high-performance, compostable packaging solutions. Relevant literature was selected through a systematic search of peer-reviewed journal articles from databases such as Scopus, ScienceDirect, and Google Scholar, focusing on publications from the last five years that addressed agricultural waste utilization in ecofriendly food packaging. The review synthesizes recent research and technological breakthroughs in this field, showcasing applications ranging from rice husk-based films to cassava starch bioplastics. Furthermore, it examines the environmental benefits of reduced plastic pollution and landfill burden, alongside the economic advantages of waste valorization, rural job creation, and market competitiveness. By turning agricultural residues into valuable resources, this approach supports circular economy principles, enhances food system sustainability, and paves the way for a greener packaging industry.